A framework for classification of snow- and icephobicity. Issue 10 (19th May 2021) - Borrebæk, Per-Olof A.; Rønneberg, Sigrid; Jelle, Bjørn Petter; Klein-Paste, Alex; Zhang, Zhiliang; He, Jianying
Abstract: For decades, there has been no proper thermodynamic definition of icephobicity. Some claim icephobic properties at an adhesion lower than 100 kPa, whereas others claim it when the accretion of ice is significantly prolonged. Herein we propose to use a terminology based on the type of frozen water deposition and its physical behaviour, separating ice and snow in adhesion and accretion. This is done in order to lay a foundation on which to introduce a framework for classification of snow- and icephobic surfaces. Such a classification empowers users and producers of such surfaces to communicate accurately about performances and expectations of surfaces and coatings. We include snowphobicity in this scheme, as snow is closely related to the traditional icephobicity and often exhibit overlapping requirements.